HUBUNGAN OBESITAS DAN PENGGUNAAN ALAT KONTRASEPSI SUNTIK DENGAN KEJADIAN KEPUTIHAN PATOLOGIS PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS SIDOMULYO KOTA BENGKULU - Alya Melindra, Tyas; Mariati; Savitri, Wewet (JURNAL BESUREK JIDAN, 2024)
Data from the World Health Organization (WHO) states that the prevalence rate in 2022 for women in the world who have experienced vaginal discharge is 75%. The purpose of the study was to determine the relationship between obesity and the use of injectable contraceptives and the incidence of pathological vaginal discharge in women of childbearing age at the Sidomulyo Health Center, Bengkulu City. This type of research is a quantitative research with a Crossectional research design. The population in this study is all WUS who visited the Sidomulyo Health Center in 2023, with a sample of 42 WUS, using the Proposive Sampling technique. The results of the study were obtained that most of the respondents were 72.2% with obesity, most of the respondents 59.5% used injectable contraceptives, most of the respondents 73.8% did not experience pathological vaginal discharge. The results of the bivariate analysis test with Chi-square obtained a p-value = ≤ α 0.05 which showed that there was a significant relationship between the use of injectable contraceptives and the incidence of pathological vaginal discharge in women of childbearing age at the Sidomulyo Health Center, Bengkulu City. It is recommended to KIA midwives to provide consultation to mothers about the use of contraceptives and obesity that are at risk of experiencing vaginal discharge, as well as other triggering factors that can increase the risk of pathological vaginal discharge. Keywords: Obesity, Use of Contraceptives, Pathological Vaginal Discharge